2021
DOI: 10.1007/s00128-021-03159-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Sediments Contaminated by Mining be a Source of Mercury in the Coastal Environment Due to Dredging? Evidence from Thermo-Desorption and Chemical Speciation

Abstract: The sediments in the Gulf of Trieste (northern Adriatic Sea, Italy) are contaminated by mercury (Hg) due to historic mining which took place in Idrija (Slovenia). Despite many studies having been done regarding Hg, no information is available on the potential impact of dredging required along the main channel approaching the Port of Monfalcone. Sixteen surface sediment samples were collected along the channel to determine both total Hg concentration and chemical species using the thermo-desorption (TD) techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…However, this perturbation lasted approximately 24 h, suggesting that it may have been related to technical operations at the mussel farm such as the lowering of a boat's anchor. The Hg concentration in the investigated surface sediments varied between 0.77 (site P1) and 6.39 (site P6) µg g −1 and the grain-size composition was consistent with previous research focused on the main channel approaching the Port of Monfalcone [30] (Table 2) showing that the surface sediments were dominated by silt, and Hg ranged between 0.30 and 13.5 µg g −1 , decreasing from the offshore area to the innermost sector of the access channel to the port area [30].…”
Section: Surface Sediments: Grain-size and Hg Contentsupporting
confidence: 90%
See 4 more Smart Citations
“…However, this perturbation lasted approximately 24 h, suggesting that it may have been related to technical operations at the mussel farm such as the lowering of a boat's anchor. The Hg concentration in the investigated surface sediments varied between 0.77 (site P1) and 6.39 (site P6) µg g −1 and the grain-size composition was consistent with previous research focused on the main channel approaching the Port of Monfalcone [30] (Table 2) showing that the surface sediments were dominated by silt, and Hg ranged between 0.30 and 13.5 µg g −1 , decreasing from the offshore area to the innermost sector of the access channel to the port area [30].…”
Section: Surface Sediments: Grain-size and Hg Contentsupporting
confidence: 90%
“…The concentration of Hg in the surface sediments investigated in this study (0.77–6.39 µg g −1 , Figure 3 ) exceeded the Italian regulatory threshold limit of 0.30 µg g −1 (Decrees of the Italian Ministry of the Environment 260/2010 and 172/2015 according to EU Directive 2000/60/EC). Although the results from this study testified to a total Hg concentration in the surface sediments which remains of concern, speciation analyses performed on sediments collected along the main access channel to the Port of Monfalcone recently demonstrated that the element appeared to be strongly associated with the less mobile chemical fractions [ 30 ]. This suggested that most of the Hg in the investigated sediments was not available for MeHg production unless under conditions of anoxia [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations